Pengembangan Game Berbasis Unity Engine Pada Cerita Perang Kembang - Muhammad, Fuad, Prof. Dr. Budi Murtiyasa, M. Kom, Dedi Gunawan, S.T., M.Sc (2017)
shooting Arcade Game development based Unity Engine and the C# languange program at the Perang Kembang Arjuna and Buto Cakil is a two dimensional computer game with Adventure as genre of the game. The story of the game is Perang Kembang as a story in the game by introducing two important characters, Arjuna as a hero and Buto Cakil as enemies. The core game itself is how the Arjuna can pass through any obstacles in each chapter inside of the game to beat Buto Cakil to reach the place for meditation. Testing was completed with a questionnaire by elementary school students and running applications on the Windows XP, Windows 7, Windows 8 and Windows 8.1, the test has obtained results that Arjuna Adventure game worthy to be a computer game for kids especially those who are still in elementary school education, this game also has a good performance after testing in different Windows operating systems